The value of 18-FDG PET/CT in the diagnosis and management of implant-related infections of the tibia: A case series. Issue 7 (July 2015) - Shemesh, S.; Kosashvili, Y.; Groshar, D.; Bernstine, H.; Sidon, E.; Cohen, N.; Luria, T.; Velkes, S.
Abstract Background Positron emission tomography (PET) combined with Computerised Tomography (CT) is gaining ground in clinical settings due to its added value of combined metabolic and anatomical imaging. PET/CT has shown promising results in diagnosing both acute and chronic infection of the axial and appendicular skeleton. PET imaging has an advantage in patients with metallic implants because FDG uptake, in contrast to magnetic resonance imaging (MRI) and standard computed tomography (CT), is not hampered by metallic artifacts. The role of PET/CT in the evaluation of implant-related infections involving the tibia in particular has not been thoroughly studied. Purpose To investigate the usefulness of 18-FDG PET/CT in the diagnosis and treatment of implant-related infections of the tibia following osteosynthesis. Methods We reviewed 10 patients who underwent internal fixation to the tibia following trauma (4 open fractures, 6 closed fractures) and presented later with clinical signs of a possible implant-related infection. In evaluating the patients we used standard work-up methods (standard radiographs, lab tests) as well as advanced imaging techniques (PET/CT) in order to confirm the diagnosis and decide upon the preferred treatment. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were then calculated for PET/CTs ability to predict presence of infection using intraoperative cultures as the gold standard. Results PET/CT validated our working diagnosis 9 out of 10 patients. In particular, it helped distinguish between: infected nonunion (n = 4), aseptic nonunion (n = 1), soft tissue infection (n = 2) and chronic osteomyelitis (n = 3). The overall sensitivity and specificity of PET/CT for identifying an osseous infection were 85.7% and 100%, respectively. The PPV and NPV were 100% and 75%, respectively. Conclusion PET/CT is a promising imaging modality that can aid in the work up of patients with suspected implant-related infections of the tibia following osteosynthesis, and may be used as a supportive measure in clinical decision making.